Bone health of joung male gymnasts: A systematic review - Burt, L. A.; Greene, D. A.; Naughton, G. A. (Pediatric Exercise Science, 2017)
Purpose: To synthesize existing literatures on the impact of gymnastics participation on the skeletal health of young male gymnasts. Methods: Following a systematic search, 12 studies were included in this review. Quality of included studies was assessed using the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE modified) criteria. Results: Assessment of skeletal health varied between and within imaging modality protocols. Gymnasts had higher total bone content, greater total and trabecular bone density, larger bone size, a thicker cortex, and higher estimates of bone strength than controls. Recreational studies reported no difference in height or weight between gymnasts and controls; however, elite gymnasts were shorter and lighter than nongymnasts. STROBE scores ranged from 65% to 95%. Conclusion: Gymnastics participation may be beneficial to the bone health of young males as gymnasts had higher bone density and bone mineral content, larger bones, and greater estimates of bone strength than controls.